ANALYSIS OF TEACHING MATERIAL NEEDS FOR SEQUENCES AND SERIES TO IMPROVE SMA/MA STUDENTS' MATHEMATICAL PROBLEM SOLVING CAPABILITY - Muliyana, Dewi; Murni, Atma; Saragih, Sehatta; Roza, Yenita (Universitas Tanjungpura, 2024)
Teaching materials are one of the supporting components for achieving mathematical problem solving abilities. This research aims to analyze the need for teaching materials regarding sequences and series to improve mathematical problem solving abilities for class at SMAN 15 Pekanbaru. Data collection through interviews and questionnaires uses instruments that contain indicators, namely learning resources, content of teaching materials, and needs for teaching materials. The data analysis used is Miles-Huberman Interactive Analysis, which consists of data condensation, data display and conclusion drawing. The results of this research indicate that the teaching materials used in learning have shortcomings, namely: the teaching materials do not use a certain approach so that the teaching materials cannot improve mathematical problem solving abilities; material is received by memorization; teaching materials are less attractive, not contextual, unclear and difficult to use if there is no teacher explanation; teaching materials cannot make students active; and teaching materials cannot yet be called teaching materials because the constituent components are still lacking. The teacher stated that learning using teaching materials was better than just using textbooks. Based on the results of the research, it is hoped that it can be followed up to overcome students' problems in using teaching materials designed by teachers and developing teaching materials on sequence and series material which can improve students' mathematical problem solving abilities